ANALISIS STRATEGI PEMUNGUTAN PIUTANG PAJAK BUMI DAN BANGUNAN TAK TERTAGIH KOTA CIMAHI - Setyanto, Eko; Ndruru, Sanida (Program Studi Magister Manajemen, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
Every year there are additional Land and Building Tax (PBB) receivables which become the work burden of the Cimahi City Regional Revenue Management Agency (Bappenda) and are recorded in the Cimahi City Regional Government's Financial Report. To reduce PBB receivables, strategies are needed and how to implement these strategies is necessary. analyzed further in order to always get new strategies that are better, more effective, efficient and economical in collecting PBB and efforts to reduce tax receivables. The research design that will be used is a descriptive analysis research method with a qualitative approach in order to broadly describe the UN collection strategy for reducing uncollectible tax receivables at the Cimahi City Bappenda. This research was conducted at the Cimahi City Bappenda which is located at the Cimahi City Public Services Mall, Jl. Aruman Kel. Pasirkaliki District. North Cimahi Cimahi City, West Java Province. Analysis was carried out starting from before being in the field, while in the field and after being in the field, using library research, field research and interviews.The results of this research produced a study and document analysis of the collection strategy for uncollectible land and building tax receivables in Cimahi City.